Regional Aspects of Stratified Employment Space - ПашининаЕкатерина Игоревна (Journal of Economic Sociology, 2010)
The goal of the paper is to identify the social and professional characteristics of employment that influence the processes of social stratification and construction of the middle class. The paper is focused on the stratified processes of employment under the conditions of unequal access to the educational, professional and power resources of the regional space. The author provides the theoretical and methodological analysis of social structure and empirical survey of professional aspects of social stratification.